Topical Rho-Associated Kinase Inhibitor, Y27632, Accelerates Corneal Endothelial Regeneration in a Canine Cryoinjury Model. Issue 3 (March 2019) - Miyagi, Hidetaka; Kim, Soohyun; Li, Jennifer; Murphy, Christopher J.; Thomasy, Sara M.
Abstract : Purpose: Corneal endothelial cell regeneration varies by species, with nonhuman primates (NHPs) and rabbits displaying low and high proliferative capacities, respectively. Recent studies report that topical application of rho-associated kinase (ROCK) inhibitors accelerates corneal endothelial wound healing in animal models and human patients with endothelial dysfunction. This study determines the regenerative capacity of canine corneal endothelial cells in vivo and their response to a topical ROCK inhibitor, Y27632, after transcorneal freezing. Methods: Right eyes of 6 beagles underwent transcorneal freezing; 10 mM ROCK inhibitor Y27632 or vehicle control was applied topically to both eyes at least 4 times daily for 56 days. Endothelial cell density was evaluated by in vivo confocal microscopy, and corneal thickness was measured by Fourier-domain optical coherence tomography (FD-OCT) and ultrasound pachymetry. Results: Transcorneal freezing induced severe central corneal edema in dogs, with restoration of transparency occurring within 4 weeks. Y27632 significantly decreased corneal thickness by FD-OCT and ultrasound pachymetry in the acute phase and significantly increased endothelial cell density at days 28 and 42 post-cryoinjury, suggesting faster restoration of endothelial cell recovery. Conclusions: Canine corneal endothelial function recovers at a similar rate as NHPs but more slowly than rabbits after cryoinjury. Faster corneal endothelial wound healing was observed by in vivo confocal microscopy and FD-OCT in dogs treated with Y27632 versus vehicle controls. Thus, a canine cryoinjury model may be a useful alternative to NHPs in detecting a response to therapies directed at endothelial regeneration. Abstract : Supplemental Digital Content is Available in the Text.